Penggunaan Media Pembelajaran Desain Grafis Melalui Aplikasi Canva - Husain Al Hidayah; Hasan Muh. Hidayatullah; Anin Asnidar; Nasir Nasir (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Learning media are all means, tools as media used in the teaching and learning process, including graphic design through thecanva application.Graphic design isacommunication processthat usesvisual elementssuchaswriting, shapes,andimagestoconvey messages.Canva is one of the applications that can be used for graphic design. This study aims to describe the use of learning media through the canva application. The research method used is descriptive qualitative. The results of the study are expected that students are ableto use graphic design learning media through thecanva application.